Analysis on the absorption of hydrogen chloride with the absorbent of Na2CO3 for dechlorinating pyrolysis of municipal solid waste - Zhang, Changfeng; Wang, Ze; Wang, Guishan; Li, Songgeng (International journal of sustainable energy, 2022)
The amount of HCl in hot volatile from pyrolysis of municipal solid waste can be decreased with absorbent. Herein, the absorption of HCl with Na 2 CO 3 was investigated by thermodynamic method and fixed-bed experiments. The results showed that CO 2 and H 2 O were inhibitive to the absorption of HCl. The role of CO 2 was stronger than that of H 2 O in lower temperatures (<730°C), while the effect of H 2 O became more distinct in higher temperatures. The performance of Na 2 CO 3 was excellent in lower temperatures, while it performed worse and the performance could not be remarkably improved by increasing the dosage of Na 2 CO 3 over 553°C. The results from experiments verified that the inhibiting effect of CO 2 was stronger than that of H 2 O at 550°C.